Enkrasia - Broome, John (Organon F, 2013)
Rationality requires you to intend to do what you believe you ought to do. This is a rough formulation of the requirement I call ‘Enkrasia’. This article presents a precise formulation. It turns out to be complicated, and the article also explains the need for each complication.
Keywords: Enkrasia; intention; ought; practical reason; rationality; requirement